The Satyricon $1 (BVolume 05: Crotona Affairss - Petronius Arbiter, 20-66; Firebaugh, W. C. (Salt Lake City, UT : Project Gutenberg, 2004)
"The Satyricon $1 (BVolume 05: Crotona Affairs" by Petronius Arbiter is a Latin work of fiction written in the late 1st century AD. This volume follows the narrator Encolpius and his companions as they navigate a world of decadence, deception, and desire. Blending prose and verse, the narrative offers satirical glimpses into Roman society through bizarre encounters and erotic adventures. The work combines serious and comic elements, creating a unique example of Menippean satire that reveals the absurdities of wealth, pretension, and human behavior in the early Roman Empire. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Satyricon
Release date is 2004-06-01
Produced by David Widger
Keywords: Rome -- Fiction; Satire, Latin -- Translations into English